BRAF mutation is not predictive of long‐term outcome in papillary thyroid carcinoma. (25th February 2015) - Henke, Lauren E.; Pfeifer, John D.; Ma, Changquing; Perkins, Stephanie M.; DeWees, Todd; El‐Mofty, Samir; Moley, Jeffrey F.; Nussenbaum, Brian; Haughey, Bruce H.; Baranski, Thomas J.; Schwarz, Julie K.; Grigsby, Perry W.
<x xml:space="preserve">Abstract</x> The BRAF mutation occurs commonly in papillary thyroid carcinoma (PTC). This is the most extensive study to date in the United States to demonstrate that BRAF mutation is of no predictive value for recurrence or survival in PTC.